(untitled) (European Journal of Behavioral Sciences, 2019)
Local wisdom is a very interesting culture of a society in Indonesia. One of the local wisdom in Indonesia is the Sumbawa community. The values of the wisdom of the Sumbawa people can be found in Sumbawa proverb. The Sumbawa proverb that is present in the Sumbawa community cannot be separated from the cultural background of the Sumbawa people. The cultural background of the community can affect the process of creating local wisdom. Semiotic linguistic studies can be used to examine the values of local wisdom in society. Semiotic is also very suitable for explaining culture. The method used in this study is qualitative. The theory used in this study is a semiotic theory of Rolland Barthes about denotation and connotation. The object of the study is Sumbawa’s proverb in two levels based on Barthes’s semiotics’ theory: (1) Denotation: the most obvious meaning of the sign; (2) Connotation: the interaction between the sign that meets the feelings or emotions of the audience and its culture. Based on the results of Roland Barthes’s semiotics through the process of denotation and connotation can be concluded that in Sumbawa proverb can be found the values of local wisdom such as the values of hard work, a relationship between human beings, a male and female character, and how is the relationship between men and women.